OPTION MARKET EFFICIENCY: A COMPREHENSIVE BIBLIOMETRIC STUDY ON RESEARCH EVOLUTION AND EMERGING THEMES - Kurian, Binu C; R, Swapna.; C R, Athira (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Purpose: This study focuses on option market efficiency, a critical area in financial derivatives impacting pricing, volatility forecasting, and risk management strategies. Utilizing bibliometric analysis with tools such as Biblioshiny and VOS viewer, this research performs a quantitative assessment of the literature on option market efficiency. By analysing 403 research papers from the Scopus database, this study aims to provide a structured overview of key themes, influential authors, and research trends, enhancing the quality of literature review within this domain. Design/Methodology/Approach: The dataset was systematically compiled from the Scopus database, following the PRISMA protocol for literature screening and selection. The chosen papers, spanning from 1978 to 2021, were analysed using Biblioshiny and VOS viewer to identify significant themes, key contributors, and core publications in option market efficiency research. A conceptual model was applied to extract prominent themes, while a thematic map visually displayed interconnections within the field. Results: The analysis revealed substantial growth in academic publications on option market efficiency, with the United States, China, and India as the most prolific contributors. High-frequency keywords, such as ’Option Market,’ ’Volatility Forecasting,’ and ’Put-Call Parity,’ were identified as core themes. Thematic mapping categorized these into motor themes, including “Option Market Dynamics” and “Volatility Management,” highlighting well-developed and central aspects of the literature. Foundational themes like "Market Microstructure" and "Transaction Costs" provide the base for future work, while emerging themes such as "Machine Learning" indicate areas of growing interest. Influential journals in this field include the Journal of Futures Markets, Journal of Financial Economics, and Journal of Banking and Finance. Originality/Value: This study employs advanced bibliometric techniques, offering valuable insights into the research landscape of option market efficiency. The integration of a conceptual model and thematic map provides a structured and innovative understanding of trends, aiding researchers and practitioners in navigating this complex field. Practical Implications: The findings present actionable insights for policymakers and practitioners by highlighting trends and gaps in the literature, supporting informed decision-making in option markets. This study also provides a foundation for future research by detailing the evolution and current focus areas within option market efficiency.